The home: a meta-factor for the promotion of resilience in situations of homelessness - Regalado Piñero, Jonathan Jesús; Torbay Betancor, Ángela Esther; Rodríguez Santana, Gustavo Mario (Cuadernos de Trabajo Social, 2021)
The scientific evidence has proven that the resilience approach is a useful and potentially effective alternative for intervention in situations of homelessness. The aim of this research is to answer certain questions regarding the relationship between resilience and homelessness, in order to establish foundations for the implementation of effective implementations with people in a situation of homelessness. The research was carried out with a sample of 120 individuals, both with and without a home. It was confirmed that residential status and resilience are related variables and that there is an inverse relationship between homelessness and resilience. Significant differences were found in levels of resilience between people in a situation of homelessness and those with a home. Another finding was that levels of resilience fell as more time was spent in situations of homelessness. One of the main conclusions of this study is that the home is a meta-factor for resilience in situations of homelessness.